A Study of Anemia Among Early Adolescent in Elementary School - Maryatun, Maryatun; Rahmawatie Ratna Budi Utami, Dyah; Haryoto, Haryoto; Husain, Fida’ (LPPM Universitas Duta Bangsa Surakarta, 2024)
Adolescents health is one of the most critical aspects of health in next step. Health problems often experienced by adolescents are anemia. Anemia is a condition in which the hemoglobin level is less than 12 mg/dl. Anemia is one of the health problems in Indonesia. Anemia in adolescence cause health disorder. If not getting the right treatment will cause reproductive health disorder. The purpose of this research is to examine the status of anemia, nutritional status and identify its characteristics. The subject of this study is elementary school students of 35 people who get from 5 and 6 grades. The research has been carried out at Jetis Elementary School. In this study, the measurement of body weight, height and Hb rate against 35 students. The results showed that the characteristics of the respondent based on the age of majority aged 11 years as much as 42.9%. The measurement results of Anthropometry showed that most are in the thin BMI status as much as 74.3. The prevalence of anaemia is 8.6% with majority are non anemia. The conclusion of this research is the incidence rate of anemia in early adolescent amounted 8.6%